Performance of Skilled Migrants in the U.S. : A Dynamic Approach - Mattoo, Aaditya (World Bank, Washington, DC, 2012)
The initial occupational placements of male immigrants in the United States labor market vary significantly by country of origin even when education and other individual factors are taken into account. Does the heterogeneity persist over time? Using data from the 1980, 1990, and 2000 Censuses, this paper finds that the performance of migrants from countries with lower initial occupational placement levels improves at a higher rate compared with that of migrants originating from countries with higher initial performance levels. Nevertheless, the magnitude of convergence suggests that full catch-up is unlikely. The impact of country specific attributes on the immigrants' occupational placement occurs mainly through their effect on initial performance and they lose significance when initial occupational levels are controlled for in the estimation.